Implant survival and patient satisfaction of reduced diameter implants made from a titanium-zirconium alloy: A retrospective cohort study with 550 implants in 311 patients. Issue 12 (December 2016) - Herrmann, Jan; Hentschel, Andreas; Glauche, Ingmar; Vollmer, Armin; Schlegel, Karl Andreas; Lutz, Rainer
Abstract: The aim of the study was to evaluate implant survival of reduced-diameter implants compared to regular-diameter implants. A retrospective evaluation of 154 Straumann Bone Level Roxolid ® implants (diameter 3.3 mm) with SLActive ® -surface in 107 patients, which were inserted between 2009 and 2010 in private practice, was performed. The mean observation period was 22.4 ± 8.2 months. 396 Straumann SLActive ® implants (4.1 mm and 4.8 mm) in 204 patients, with an observation period of 28.4 ± 10.1 months served as control group. Implant survival rate, resonance frequency analysis and patient satisfaction were evaluated. The implant survival rate was 97.4% in the test vs. 98.5% in the control group. Resonance frequency analysis showed statistically significant lower values for the reduced-diameter implants. Patient satisfaction showed no significant difference between the test and the control group. Reduced-diameter implants displayed high survival rates during the period investigated and represent a convincing treatment alternative. Long-term follow-up investigations confirmed the high implant survival rates of 96.8% (after 69.7 ± 12.3 months) in the test group and 98.5% (after 76.0 ± 13.6 months) in the control group.